Graphite negative electrode material and preparation method and application thereof
By covering the ionic polymer and lithium salt on the surface of the graphite negative electrode material, the problem of poor battery performance after the polymer is coated with graphite is solved, and higher first discharge specific capacity, Coulomb efficiency and cycling stability are achieved.
Patent Information
- Application Number
- CN202411972337.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
In the prior art, after the polymer is coated with graphite, the first discharge specific capacity, first Coulomb efficiency and cycle stability still need to be improved.
Artificial graphite is used and the coating layer composed of ionic polymer and lithium salt is uniformly coated on its surface to form a stable artificial solid electrolyte interface (SEI) to improve the overall performance of the battery.
It significantly improves the first discharge specific capacity, first Coulomb efficiency and cycle stability of graphite negative electrode materials, extends the cycle life of the battery and improves the overall performance of the battery.
Smart Images

Figure BDA0005220399220000051 
Figure BDA0005220399220000091
Abstract
Description
Technical Field
[0001] The invention relates to a graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of electric vehicles and renewable energy storage systems, the importance of lithium-ion batteries in the field of energy storage has become increasingly prominent. Graphite, as a traditional negative electrode material, is widely used due to its good conductivity and reversibility. However, during high-rate charge and discharge, graphite negative electrodes often face problems of capacity decay and poor cycle stability, which is mainly attributed to the volume change of lithium ions during charge and discharge and the formation of unstable solid electrolyte interface (SEI).
[0003] During the charging process of traditional lithium-ion batteries, the electrolyte decomposes to form a SEI film on the graphite surface, which consumes lithium ions and reduces the initial coulomb efficiency. As the battery continues to cycle, the expansion of the graphite negative electrode will cause the naturally generated SEI to break.
[0004] In recent years, research on constructing an artificial SEI layer has gradually received attention. By coating graphite with polymers, the formation of SEI can be effectively regulated, the interface stability can be improved, and the overall performance of the battery can be improved. Polymer coating can not only provide mechanical protection for the graphite negative electrode and reduce the volume expansion during the insertion and deintercalation of lithium ions, but also regulate ion conduction and interface reactions to form a more ideal SEI layer. Such a design aims to enhance the cycle life and safety of the battery and provide new ideas for the development of high-performance lithium-ion batteries. Therefore, the research on polymer-coated graphite negative electrodes to construct artificial SEI has important theoretical significance and practical application value. However, the first coulombic efficiency after polymer coating of graphite in the prior art still needs to be improved. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the defects in the prior art that the first discharge specific capacity, first coulombic efficiency and cycle stability of polymer-coated graphite still need to be improved, and to provide a graphite negative electrode material and a preparation method and application thereof. The graphite negative electrode material of the present invention has excellent first discharge specific capacity, first coulombic efficiency and cycle stability.
[0006] The present invention provides a graphite negative electrode material, which comprises artificial graphite and a coating layer uniformly coated on the surface of the artificial graphite, wherein the coating layer comprises an ion-conducting polymer and a lithium salt; the mass ratio of the artificial graphite to the ion-conducting polymer is 100:(1.8-10); the mass ratio of the artificial graphite to the lithium salt is 100:(0.1-0.25).
[0007] In the present invention, preferably, the particle size D50 of the artificial graphite is 6-8 μm, for example 7.25 μm.
[0008] In the present invention, preferably, the aggregate Coulomb efficiency of the artificial graphite is greater than 90%, such as 91%.
[0009] In the present invention, preferably, the ion-conducting polymer is polyethylene oxide or polyurethane; the polyethylene oxide is, for example, polyethylene glycol; the polyurethane is, for example, water-based polyurethane.
[0010] The molecular weight of the polyethylene glycol is preferably 18000-22000, for example 20000. In one embodiment of the present invention, the polyethylene glycol is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and its product number is P432531.
[0011] In one embodiment of the present invention, the waterborne polyurethane is purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a product number of W909579.
[0012] In the present invention, preferably, the lithium salt is selected from one or more of LiPF6, LiTFSI, LiBF4 and Li3PO4, for example, LiPF6 or LiTFSI.
[0013] In the present invention, preferably, the mass ratio of the artificial graphite to the ion-conducting polymer is 100:(1.8-5), for example, 100:1.8.
[0014] In the present invention, preferably, the mass ratio of the artificial graphite to the lithium salt is 100:(0.15-0.25), for example, 100:0.2.
[0015] In the present invention, preferably, the mass ratio of the ion-conducting polymer to the lithium salt is (7.2-20):1, for example, 9:1.
[0016] The present invention also provides a method for preparing a graphite negative electrode material, which comprises the following steps: uniformly mixing artificial graphite and a polymer solution, and drying;
[0017] Wherein, the polymer solution comprises an ion-conducting polymer, a lithium salt and a solvent; the mass ratio of the artificial graphite to the ion-conducting polymer is 100:(1.8-10); the mass ratio of the artificial graphite to the lithium salt is 100:(0.1-0.25).
[0018] In the present invention, preferably, the particle size D50 of the artificial graphite is 6-8 μm, for example 7.25 μm.
[0019] In the present invention, preferably, the aggregate Coulomb efficiency of the artificial graphite is greater than 90%, such as 91%.
[0020] In the present invention, preferably, the ion-conducting polymer is polyethylene oxide or polyurethane; the polyethylene oxide is, for example, polyethylene glycol; the polyurethane is, for example, water-based polyurethane.
[0021] The molecular weight of the polyethylene glycol is preferably 18000-22000, for example 20000. In one embodiment of the present invention, the polyethylene glycol is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and its product number is P432531.
[0022] In one embodiment of the present invention, the waterborne polyurethane is purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a product number of W909579.
[0023] In the present invention, preferably, the lithium salt is selected from one or more of LiPF6, LiTFSI, LiBF4 and Li3PO4, for example, LiPF6 or LiTFSI.
[0024] In the present invention, preferably, the solvent is water and / or an organic solvent, the water is, for example, deionized water, and the organic solvent is, for example, ethanol and / or acetonitrile.
[0025] In the present invention, preferably, the mass ratio of the artificial graphite to the ion-conducting polymer is 100:(1.8-5), for example, 100:1.8.
[0026] In the present invention, preferably, the mass ratio of the artificial graphite to the lithium salt is 100:(0.15-0.25), for example, 100:0.2.
[0027] In the present invention, preferably, the mass ratio of the ion-conducting polymer to the lithium salt is (7.2-20):1, for example, 9:1.
[0028] In the present invention, preferably, the ratio of the mass of the artificial graphite to the volume of the solvent is 1 g: (1.2-3) mL, for example, 1 g: 1.8 mL.
[0029] In the present invention, the ion-conducting polymer and the lithium salt in the polymer solution are in a clear state. The polymer solution is prepared, for example, by the following preparation method: dissolving the ion-conducting polymer and the lithium salt in the solvent, and stirring to completely dissolve the ion-conducting polymer and the lithium salt.
[0030] In the present invention, preferably, the mixing further comprises a stirring operation; the stirring is used to uniformly disperse the artificial graphite in the polymer solution; and the stirring time is a conventional time in the art.
[0031] In the present invention, preferably, the drying further includes an evaporation operation, and the evaporation operation is performed in a water bath, for example.
[0032] In the present invention, preferably, the drying is spray drying or vacuum drying; the drying is used to remove the solvent.
[0033] Preferably, the vacuum drying temperature is 120-180°C, for example, 150°C.
[0034] The vacuum drying time is conventional in the art, for example, 8-15 hours, for example, 10 hours.
[0035] The present invention also provides a graphite negative electrode material, which is prepared by the above-mentioned method for preparing the graphite negative electrode material.
[0036] The present invention also provides a use of the graphite negative electrode material as described above in a lithium ion battery.
[0037] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0038] The reagents and raw materials used in the present invention are commercially available.
[0039] The positive and progressive effects of the present invention are:
[0040] The graphite negative electrode material of the invention has excellent first discharge specific capacity, first coulomb efficiency and cycle stability.
[0041] The graphite negative electrode material of the present invention is coated with a coating layer uniformly on the surface of artificial graphite, and the coating layer includes an ion-conducting polymer and a lithium salt to form a stable artificial SEI. The flexibility of the ion-conducting polymer film solves the problem that the naturally generated SEI film is easily damaged, and improves the ion conductivity and electrochemical stability of the electrode material, thereby improving the overall performance of the battery. The lithium salt in the coating layer improves the conduction efficiency of lithium ions, reduces the corrosion and precipitation of lithium metal, and the addition of lithium salt can effectively supplement the consumed lithium ions, further improving the initial coulomb efficiency. In addition, the ion-conducting polymer and artificial graphite are combined to form a composite material, which not only improves the conductivity, but also enhances the mechanical strength and chemical stability, and improves the cycle life of the battery. DETAILED DESCRIPTION
[0042] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0043] The main raw material information involved in the examples and comparative examples of the present invention is shown in Table 1:
[0044] Table 1
[0045]
[0046] Example 1
[0047] This embodiment provides a graphite negative electrode material, and the preparation method thereof includes the following steps:
[0048] 1. Add 9 g of polyethylene glycol and 1 g of LiPF6 into 900 mL of water and stir for 20 min to completely dissolve them to obtain a polymer solution.
[0049] 2. Slowly add 500 g of artificial graphite to the polymer solution while stirring, and continue stirring for 60 minutes until the graphite is evenly dispersed. Evaporate in a water bath to obtain a viscous slurry.
[0050] 3. The slurry was placed in a vacuum oven and dried at a constant temperature of 150°C for 10 hours to dry out the water to obtain a graphite negative electrode material coated with a polymer and a lithium salt.
[0051] Example 2
[0052] This embodiment provides a graphite negative electrode material, and the preparation method thereof includes the following steps:
[0053] 1. Add 9 g of waterborne polyurethane and 1 g of LiPF6 into 900 mL of water and stir for 20 min to completely dissolve them to obtain a polymer solution.
[0054] 2. Slowly add 500 g of artificial graphite to the polymer solution while stirring, and continue stirring for 60 minutes until the graphite is evenly dispersed. Evaporate in a water bath to obtain a viscous slurry.
[0055] 3. The slurry was placed in a vacuum oven and dried at a constant temperature of 150°C for 10 hours to dry out the water to obtain a graphite negative electrode material coated with a polymer and a lithium salt.
[0056] Example 3
[0057] This embodiment provides a graphite negative electrode material, and the preparation method thereof includes the following steps:
[0058] 1. Add 9 g of polyethylene glycol and 1 g of LiTFSI into 900 mL of water and stir for 20 min to completely dissolve them to obtain a polymer solution.
[0059] 2. Slowly add 500 g of artificial graphite to the polymer solution while stirring, and continue stirring for 60 minutes until the graphite is evenly dispersed. Evaporate in a water bath to obtain a viscous slurry.
[0060] 3. The slurry was placed in a vacuum oven and dried at a constant temperature of 150°C for 10 hours to dry out the water to obtain a graphite negative electrode material coated with a polymer and a lithium salt.
[0061] Comparative Example 1
[0062] This comparative example provides a graphite negative electrode material, and the preparation method thereof is as follows:
[0063] 1. Add 9 g of polyethylene glycol and 1 g of LiPF6 into 900 mL of water and stir for 20 min to completely dissolve them to obtain a polymer solution.
[0064] 2. Slowly add 500 g of natural graphite to the polymer solution while stirring, and continue stirring for 60 minutes until the graphite is evenly dispersed. Evaporate in a water bath to obtain a viscous slurry.
[0065] 3. The slurry was placed in a vacuum oven and dried at a constant temperature of 150°C for 10 hours to dry out the water to obtain a graphite negative electrode material coated with a polymer and a lithium salt.
[0066] Comparative Example 2
[0067] This comparative example provides a graphite negative electrode material, and the preparation method thereof is as follows:
[0068] 1. Add 9g polyethylene glycol to 900mL water and stir for 20min to completely dissolve it. to the polymer solution.
[0069] 2. Slowly add 500 g of artificial graphite to the polymer solution while stirring, and continue stirring for 60 minutes until the graphite is evenly dispersed. Evaporate in a water bath to obtain a viscous slurry.
[0070] 3. The slurry was placed in a vacuum oven and dried at a constant temperature of 150°C for 10 hours to dry out the water to obtain a graphite negative electrode material coated with a polymer and a lithium salt.
[0071] Comparative Example 3
[0072] This comparative example provides a graphite negative electrode material, and the preparation method thereof is as follows:
[0073] 1. Add 1g LiPF6 into 900mL water and stir for 20min to completely dissolve it to obtain a polymer solution.
[0074] 2. Slowly add 500 g of artificial graphite to the polymer solution while stirring, and continue stirring for 60 minutes until the graphite is evenly dispersed. Evaporate in a water bath to obtain a viscous slurry.
[0075] 3. The slurry was placed in a vacuum oven and dried at a constant temperature of 150°C for 10 hours to dry out the water to obtain a graphite negative electrode material coated with a polymer and a lithium salt.
[0076] Comparative Example 4
[0077] This comparative example provides a graphite negative electrode material, and the preparation method thereof is as follows:
[0078] 1. Slowly add 500 g of artificial graphite into 900 mL of deionized water while stirring, and continue stirring for 60 min until the graphite is evenly dispersed. Evaporate in a water bath to obtain a viscous slurry.
[0079] 2. The slurry was placed in a vacuum oven and dried at a constant temperature of 150°C for 10 hours to dry out the water to obtain a graphite negative electrode material coated with a polymer and a lithium salt.
[0080] Comparative Example 5
[0081] This embodiment provides a graphite negative electrode material, and the preparation method thereof includes the following steps:
[0082] 1. Add 7.5 g polyethylene glycol and 1 g LiPF6 into 900 mL water and stir for 20 min to completely dissolve them to obtain a polymer solution.
[0083] 2. Slowly add 500 g of artificial graphite to the polymer solution while stirring, and continue stirring for 60 minutes until the graphite is evenly dispersed. Evaporate in a water bath to obtain a viscous slurry.
[0084] 3. The slurry was placed in a vacuum oven and dried at a constant temperature of 150°C for 10 hours to dry out the water to obtain a graphite negative electrode material coated with a polymer and a lithium salt.
[0085] Comparative Example 6
[0086] This embodiment provides a graphite negative electrode material, and the preparation method thereof includes the following steps:
[0087] 1. Add 9 g of polyethylene glycol and 1.5 g of LiPF6 into 900 mL of water and stir for 20 min to completely dissolve them to obtain a polymer solution.
[0088] 2. Slowly add 500 g of artificial graphite to the polymer solution while stirring, and continue stirring for 60 minutes until the graphite is evenly dispersed. Evaporate in a water bath to obtain a viscous slurry.
[0089] 3. The slurry was placed in a vacuum oven and dried at a constant temperature of 150°C for 10 hours to dry out the water to obtain a graphite negative electrode material coated with a polymer and a lithium salt.
[0090] Effect Example
[0091] The particle size and electrochemical performance of the graphite negative electrode materials obtained in the embodiment and the comparative example were tested respectively.
[0092] 1. Test method for particle size Dmin, D50 and Dmax
[0093] Malvern laser particle size tester MS3000 was used to test the particle size range and distribution of the material.
[0094] 2. Test methods for electrochemical performance
[0095] The graphite negative electrode material prepared in each embodiment and comparative example is coated on a copper foil, and vacuum dried and rolled to prepare a negative electrode sheet; a commercial lithium cobalt oxide electrolyte is used, a polypropylene microporous membrane is used as a diaphragm, and a metal lithium sheet is used as a positive electrode, and a button battery is assembled in an inert gas glove box system filled with argon. The button battery is charged and discharged on a battery testing system. At room temperature, 0.1C constant current charging and discharging, the charge and discharge voltage is limited to 0.005-1.5V. The cycle stability is the ratio of its specific capacity to the initial specific capacity after 10 charge and discharge cycles under the same test conditions. The lower the value, the faster the capacity decreases and the worse the cycle stability. The charge and discharge test of the button battery is carried out on the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.
[0096] The graphite negative electrode material prepared in each embodiment and comparative example is coated on a copper foil, and vacuum dried and rolled to prepare a negative electrode sheet; commercial lithium cobalt oxide is used as the electrolyte, a polypropylene microporous membrane is used as the diaphragm, and a metal lithium sheet is used as the positive electrode, and a button battery is assembled in an inert gas glove box system filled with argon. Under normal temperature conditions, the charge and discharge test of the button battery is carried out on the battery testing system, 0.1C constant current charge and discharge, and the charge and discharge voltage is limited to 0.005~1.5V. The first discharge specific capacity and the first coulomb efficiency are both obtained in the first cycle. The cycle stability is to compare the proportion of its specific capacity to the initial specific capacity after 10 charge and discharge cycles under the same test conditions. The lower the value, the faster the capacity decreases and the worse the cycle stability. The charge and discharge test of the button battery was completed on the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.
[0097] The electrochemical performance parameters of the graphite negative electrode materials obtained in Examples 1-3 and Comparative Examples 1-6 are shown in Table 2 below:
[0098] Table 2
[0099]
[0100] As can be seen from Table 2, the first discharge specific capacity, first coulomb efficiency and 10-cycle capacity retention rate of the graphite negative electrode materials of Examples 1-3 of the present invention are better than those of Comparative Examples 1-6.
Claims
1. A graphite negative electrode material, characterized in that: It includes artificial graphite and a coating layer uniformly coated on the surface of the artificial graphite, wherein the coating layer includes an ion-conducting polymer and a lithium salt; the mass ratio of the artificial graphite to the ion-conducting polymer is 100:(1.8-10); the mass ratio of the artificial graphite to the lithium salt is 100:(0.1-0.25).
2. The graphite negative electrode material according to claim 1, characterized in that It meets one or more of the following conditions: (1) The particle size D50 of the artificial graphite is: 6-8 μm, for example 7.25 μm; (2) The aggregate Coulomb efficiency of the artificial graphite is greater than 90%, for example 91%; (3) The ion-conducting polymer is polyethylene oxide or polyurethane; the polyethylene oxide is, for example, polyethylene glycol; the polyurethane is, for example, water-based polyurethane; The molecular weight of the polyethylene glycol is preferably 18000-22000, for example 20000; The waterborne polyurethane is purchased from Shanghai MacLean Biochemical Technology Co., Ltd., and its product number is W909579; (4) The lithium salt is selected from one or more of LiPF6, LiTFSI, LiBF4 and Li3PO4, for example, LiPF6 or LiTFSI.
3. The graphite negative electrode material according to claim 1, characterized in that It meets one or more of the following conditions: (1) The mass ratio of the artificial graphite to the ion-conducting polymer is 100:(1.8-5), for example, 100:1.8; (2) The mass ratio of the artificial graphite to the lithium salt is 100:(0.15-0.25), for example, 100:0.2; (3) The mass ratio of the ion-conducting polymer to the lithium salt is (7.2-20):1, for example, 9:
1.
4. A method for preparing a graphite negative electrode material, characterized in that: The method comprises the following steps: uniformly mixing artificial graphite and polymer solution, and drying; Wherein, the polymer solution comprises an ion-conducting polymer, a lithium salt and a solvent; the mass ratio of the artificial graphite to the ion-conducting polymer is 100:(1.8-10); the mass ratio of the artificial graphite to the lithium salt is 100:(0.1-0.25).
5. The method for preparing a graphite negative electrode material according to claim 4, characterized in that: It meets one or more of the following conditions: (1) The particle size D50 of the artificial graphite is: 6-8 μm, for example 7.25 μm; (2) The aggregate Coulomb efficiency of the artificial graphite is greater than 90%, for example 91%; (3) The ion-conducting polymer is polyethylene oxide or polyurethane; the polyethylene oxide is, for example, polyethylene glycol; the polyurethane is, for example, water-based polyurethane; (4) The lithium salt is selected from one or more of LiPF6, LiTFSI, LiBF4, and Li3PO4, for example, LiPF6 or LiTFSI; (5) The solvent is water and / or an organic solvent. The water is, for example, deionized water. The organic solvent is, for example, ethanol and / or acetonitrile.
6. The method for preparing a graphite negative electrode material according to claim 5, characterized in that: It satisfies the following conditions (1) and / or (2): (1) The molecular weight of the polyethylene glycol is 18000-22000, for example, 20000; (2) The waterborne polyurethane was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with the product number W909579.
7. The method for preparing a graphite negative electrode material according to claim 4, characterized in that: (1) The mass ratio of the artificial graphite to the ion-conducting polymer is 100:(1.8-5), for example, 100:1.8; (2) The mass ratio of the artificial graphite to the lithium salt is 100:(0.15-0.25), for example, 100:0.2; (3) The mass ratio of the ion-conducting polymer to the lithium salt is (7.2-20):1, for example, 9:1; (4) The ratio of the mass of the artificial graphite to the volume of the solvent is 1 g:(1.2-3) mL, for example, 1 g:1.8 mL.
8. The method for preparing a graphite negative electrode material according to claim 4, characterized in that: It satisfies the following conditions (1) and / or (2): (1) The mixing also includes a stirring operation; (2) The drying step also includes an evaporation operation, which is performed, for example, in a water bath; (3) The drying is spray drying or vacuum drying; Preferably, the vacuum drying temperature is 120-180°C, for example, 150°C; The vacuum drying time is, for example, 8-15 hours, for example, 10 hours.
9. A graphite negative electrode material, characterized in that: The negative electrode material is prepared by the method for preparing the graphite negative electrode material as described in any one of claims 4 to 8.
10. Use of the graphite negative electrode material as claimed in any one of claims 1 to 3 or claim 9 in a lithium ion battery.
Citation Information
Patent Citations
Lithium ion battery having high initial coulombic efficiency
CN106785007A
Fast charge graphite negative electrode material and preparation method thereof
CN107601490A
Method for preparing negative electrode paste of lithium ion batteries
CN107785545A
High-energy-density fast-charging graphite composite material and preparation method thereof
CN113764646A
Ternary battery preparation method adopting graphite microchip composite positive electrode material
CN113921770A